Cat kid comic club: collaborations - Pilkey, Dav, 1966-; Pilkey, Dav, 1966-; Garibaldi, Jose (New York : Graphix / An Imprint of Scholastic, 2022)
"Naomi, Melvin, Flippy, Li'l Petey, Molly, and nineteen baby frog siblings return in a new book in the hilarious and heartwarming Cat Kid Comic Club series"--
1. Becoming a qualified nurse; 2. Being in Charge; 3. Being a good nurse; 4. Making ethical decisions; 5. Making legal decisions; 6. Working with others; 7. Teaching junior staff; 8. Getting the job; 9. Continuing professional development; 10. Putting it all together
INCLUDES INDEX
Ages 7 and Up
Grades 2-3